Comparative Study of Inflammatory Cytokine Levels and Thrombocytopenia during Plasmodium Falciparum and P. Vivax Infections: Investigating the Relationship between Inflammatory Cytokines and Thrombocytopenia during Malarial Infections (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The most commonly observed complication of malaria infections is trombocytopenia. The point of this study was to understand the possible relationship between P. vivax, P. falciparum’s notorious cytokines and blended infections across various degrees of thrombocytopenia. A hospital-based cross-sectional study was performed in India. In this study, blood samples from 627 patients with Maalria fever were examined for contaminated parasite species, clinical conditions, platelet levels and key cytokines produced in response to disease samples from 176 uninfected solid people were utilized as controls. Approximately 62.7 of patients had gentle to direct levels of thrombocytopenia and 16 had serious thrombocytopenia (platelets